Effect of the type of packaging on the shelf life of ground rabbit meat - Redondo Solano, Mauricio (2021)
Rabbit meat consumption has increased worldwide due to its health benefits in humans but few studies addressed the stability of this food matrix. The effect of two types of packaging (vacuum, VP; and polystyrene tray overwrap with PVC/polyvinyl plastic film, PT) was evaluated on the microbial stability (psychrotrophic; PSY, lactic acid bacteria; LAB, initial coliforms counts) and physicochemical (pH, thiobarbituric acid reactive substances (TBARS), total volatile basic Nitrogen (TBV-N), color and drip loss) changes of ground rabbit meat during its storage at 4 1 C. VP packaging delayed PSY growth, lipid oxidation, protein degradation and undesirable color changes compared to PT samples. Shelf life of ground rabbit meat in vacuum condition could be around 10 days of storage, while PT samples presented a shorter shelf life of around 5 days. However, sensory studies must be performed in order to assure the exact shelf life of the final product.